The new tango of Astor Piazzolla : Tanguedia Quintet LIVE - Tanguedia Quintet; Ainali, Suvi; Kataja, Iikka; Kivelä, Jani; Rantala, Olli; Sandås, Henrik (Tanguedia Quintet, 2009)
10 teosta.
Keywords: tangot (sävellykset); Suomi